Responsividade e interpretabilidade do WHODAS 2.0 para avaliação da incapacidade após um programa de reabiltação em indivíduos com condições de saúde respiratórias crônicas - Lopes, Chayenne Chylld Cesar (2024)
Introduction: Individuals with chronic respiratory health conditions have impairments that lead to disability, but which can be alleviated with physical exercise. With the purpose of measuring disability, the World Health Organization Disability Assessment Schedule (WHODAS) 2.0 was created, an instrument based on a biopsychosocial model. Objective: To analyze the responsiveness and interpretability of WHODAS 2.0 for measuring disability after a rehabilitation program with physical exercise in individuals with chronic respiratory health conditions. Methods: Prospective study with individuals with chronic respiratory health conditions who participated in a rehabilitation program offered by an extension project of a public university in Fortaleza-CE, Brazil. The program included mainly aerobic and strength exercises, performed twice a week for eight weeks. General characteristics, disability (WHODAS 2.0 with 12 questions, with a total score ranging from 0 to 100) and health-related quality of life (Saint George's Respiratory Questionnaire - SGRQ, with a score ranging from 0 to 100), among other variables, were evaluated before and after the rehabilitation program. For interpretability, the objective was to investigate a minimum important difference (MID) value, based on anchor-based and distribution-based methods. Results: Thirty-three participants were included, mean age 59 ± 17 years, 67% female, most with chronic obstructive pulmonary disease (COPD) (61%). There was a reduction in the mean WHODAS 2.0 summary score (-9.49, 95% CI -13.90 to -5.08) and in the SGRQ total score (-15.5, 95% CI -21.7 to -9.7) (p<0.001 for both) between before and after rehabilitation. There was a regular correlation between these two changes (rs=0.36; p=0.04). Using anchor-based and distribution-based methods, the MID estimate for WHODAS 2.0 ranged from -6.22 to -5.02. Conclusion: WHODAS 2.0 was shown to be responsive to an exercise rehabilitation program in individuals with chronic respiratory conditions, and a reduction of at least -6.22 is considered clinically important. These findings reinforce the clinical relevance of WHODAS 2.0 as an instrument to measure the positive impact of this intervention in this population.